2019
DOI: 10.1016/j.jmig.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Superior Hypogastric Blocks for Postoperative Pain Management in Hysterectomies: A New Technique for Superior Hypogastric Blocks

Abstract: Intraoperative SHP block is a preferable modality for postoperative analgesia in patients undergoing hysterectomy. The surgical laparoscopic modified anterior approach we describe is an uncomplicated and easily applicable method. More effective results would be seen if used together with wound site local anesthetic infiltration or abdominal wall plane blocks. (Clinical trial registration no. NCT03427840.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
(25 reference statements)
0
23
0
Order By: Relevance
“…This demonstrated intra-abdominal access to the SHP as opposed to previous CT percutaneous guidance. A later observational trial by Atyuluk was the first clinical trial to examine SHPB at laparoscopy (20). The positive results from this trial paving the way for our RCT.…”
Section: Discussionmentioning
confidence: 93%
“…This demonstrated intra-abdominal access to the SHP as opposed to previous CT percutaneous guidance. A later observational trial by Atyuluk was the first clinical trial to examine SHPB at laparoscopy (20). The positive results from this trial paving the way for our RCT.…”
Section: Discussionmentioning
confidence: 93%
“…There are limited data supporting the effectiveness of this technique in patients requiring MIGS. The only study, a single nonrandomized prospective trial, suggested that SHP may reduce postoperative pain along with opioid and NSAID consumption [112]. The complexities of this procedure, the required surgeon learning curve, and the potential associated risks preclude its widespread use.…”
Section: Regional Blocksmentioning
confidence: 99%
“…A few studies have investigated SHP block in patients undergoing a hysterectomy ( 11 - 13 ). Aytuluk et al reported that patients who were administered SHP block when undergoing laparoscopic hysterectomy had significantly lower VAS scores 1, 6, 12, 24, and 48 hours postoperatively ( 12 ). We also found significantly lower VAS scores in the SHP block group 2, 6, 24, and 48 hours postoperatively after a cesarean section.…”
Section: Discussionmentioning
confidence: 99%